Effect of perioperative COX-2 and beta-adrenergic inhibition on 5-year disease-free-survival in colorectal cancer: A pilot randomized controlled Colorectal Metastasis PreventIon Trial (COMPIT). Issue 3 (March 2023) - Ricon-Becker, Itay; Haldar, Rita; Shabat Simon, Maytal; Gutman, Mordechai; Cole, Steve W.; Ben-Eliyahu, Shagmar; Zmora, Oded
Abstract: Introduction: Based on translational and epidemiological evidence, perioperative inhibition of beta-adrenergic and COX2 signaling can reduce the risk for post-surgical metastatic disease. Here we aimed to assess in a pilot study the impact of a perioperative combined COX-2 and beta-adrenergic blockade on long-term cancer outcomes in colorectal cancer patients undergoing curative surgery. Materials and methods: Thirty-four newly diagnosed colorectal cancer patients without evidence of metastases enrolled in this double-blinded placebo-controlled randomized clinical trial (treatment, n = 16; placebo, n = 18). A 20-day oral treatment of propranolol and etodolac regimen was initiated 5 days before surgery. Beneficial effects on short-term molecular biomarkers of cancer progression were reported earlier. Here we present outcomes of five postoperative years of disease-free-survival and overall survival. Results: Adverse event rates were equivalent between the two groups. Intent-to-treat analyses of 5-year follow-up showed that 2/16 (12.5%) vs 9/18 (50%) patients exhibited recurrence in treatment vs placebo groups, respectively (p = 0.033), and 2/16 (12.5%) vs 4/18 (22%) died (p = 0.467). In protocol compliant patients 0/11 (0%) vs. 8/17 (47%) exhibited recurrence in treatment vs. placebo groups, respectively (p = 0.007), and 0/11 (0%) and 3/17 (17.6%) died (p = 0.151). Conclusions: In this pilot clinical trial, a combined perioperative treatment with propranolol and etodolac significantly improved 5-year disease-free-survival. The small sample size and a single center study design merits caution in interpreting these results, specifically in estimating the effect-size. Larger studies in colorectal cancer are warranted and needed.